Fabrication of Aluminium AA7075 Reinforced by Zinc Metal Matrix Composites and Their Wear Behaviour Analysis - Dinesh, M.; Ravindran, R. (Металлофизика и новейшие технологии, 2017)
In this study, we report effects of zinc on casted aluminium 7075 by using of stir casted method. The volume fraction of composites is prepared by density method. Stir casted composites are fabricated in different volume-fraction levels. Microstructure analysis of alloy and nanocomposites are performed by using SEM. Dry sliding wear is measured on pin-on-disc testing apparatus at various testing conditions for alloy and nanocomposite materials. As shown with the obtained results, the wear resistance increases with increasing the wt.% of reinforcing zinc nanoparticles. The different volume fractions of fabricated composites are shown, which leads to decreasing the wear rate from 40% to 60%. The nanoparticles’ sizes, microstructure, and wear rate are approximated from high-resolution diffraction analysis. Данная работа посвящена исследованию влияния цинка на литой алюминий 7075 при использовании метода литья с перемешиванием. Объёмная доля композитов подготовлена методом уплотнения. Перемешанные литые композиты изготовлены при различных уровнях объёмной доли допанта. Микроструктурный анализ сплавов и нанокомпозитов выполнен с помощью СЭМ. Износ из-за сухого скольжения для сплавов и нанокомпозитных материалов определяли на штифт-диск-аппарате при различных условиях испытаний. Результаты исследований свидетельствуют, что сопротивление износу растёт при увеличении масс.% упрочняющих наночастиц цинка. Наблюдалась различная объёмная доля изготовленных композитов, что приводило к уменьшению коэффициента износа с 40% до 60%. Размеры наночастиц, микроструктура и скорость износа согласуются с данными высокоразрешающего дифракционного анализа. Дана робота стосується дослідження впливу цинку на литий алюміній 7075 при використанні методи лиття з перемішуванням. Об’ємну частку композитів підготовлено методою ущільнення. Перемішані литі композити виготовлено за різних рівнів об’ємної частки допанту. Мікроструктурну аналізу стопів і нанокомпозитів виконано за допомогою СЕМ. Зношування сухого ковзання для стопів і нанокомпозитних матеріялів визначали на штифт-диск-апараті за різних умов випробувань. Результати досліджень свідчать, що опір зношуванню зростає при збільшені мас.% зміцнювальних наночастинок цинку. Спостерігалася різна об’ємна частка виготовлених композитів, що приводило до зменшення коефіцієнту зношування з 40% до 60%. Розміри наночастинок, мікроструктура і швидкість зношування узгоджуються з даними високороздільчої дифракційної аналізи.